1991
DOI: 10.1149/1.2085404
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tungsten Alloying Additions on the Passivity of Aluminum

Abstract: Transition metals such as Mo, W, Ta, Cr, and W can be used to significantly enhance the localized corrosion resistance of A1. Since these elements exhibit very low solubilities in aluminum, a nonequilibrium alloying method, such as sputter deposition, must be used to produce single-phase alloys. The addition of approximately 9 atom percent W to A1 can shift its pitting potential in the positive direction as much as 2600 mV. Heat-treatment of these nonequilibrium alloys results in the precipitation of a second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
61
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 30 publications
6
61
0
Order By: Relevance
“…• C in the equilibrium state, 2 the formation of Al-W alloy films having high corrosion resistances requires non-equilibrium processes, such as sputtering, 1,[3][4][5][6][7][8] ion implantation, 9 and electrodeposition. [10][11][12] Of these methods, electrodeposition has particular advantages in that a uniform film can be formed relatively quickly and continuously, onto substrates having complex shapes, using simple equipment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…• C in the equilibrium state, 2 the formation of Al-W alloy films having high corrosion resistances requires non-equilibrium processes, such as sputtering, 1,[3][4][5][6][7][8] ion implantation, 9 and electrodeposition. [10][11][12] Of these methods, electrodeposition has particular advantages in that a uniform film can be formed relatively quickly and continuously, onto substrates having complex shapes, using simple equipment.…”
mentioning
confidence: 99%
“…Reports on the electrodeposition of Al alloys including Al-Ni, 13 Al-Ti, 14 Al-V, 15 Al-Zr, 16 Al-Mo, 17 Al-Mn, 18 and Al-Hf 19 are available in the literature. A previous study revealed that electrodeposition in a EMIC-AlCl 3 bath with the addition of W(IV) chloride (WCl 4 ) yielded Al-W alloys, but the W content was lower than 1 at.%. 10 Recently, the electrodeposition of Al-W alloy films from an EMIC-AlCl 3 bath with the addition of the W(III) compound K 3 W 2 Cl 9 was reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (1996Lee et al ( , 1997 reported a beneficial effect of tantalum to improve the corrosion resistance of nickelbase alloys in 12 M HCl. A series of the sputterdeposited binary tantalumcontaining alloys showed higher corrosion resistance than those of alloying elements due to spontaneous passivation in aggressive media (Shaw et al 1991, Yoshioka et al 1991, Kim et al 1994, El Moneim et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Among the non-equilibrium binary alloys, it is well-known that Al-W prepared by the physical non-equilibrium alloying methods described above show the most anodic chloride-induced pitting corrosion potential. [20][21][22][23][24] When the W content of these alloys exceeds ca. 10 atomic percent (a/o), the passive region of the Al-W alloy extends to nearly +2,600 mV against pure aluminum.…”
mentioning
confidence: 99%